Isolated bilateral molariform mandibular second premolars; a case report - Maryam Zangoei Booshehri; Hamid Reza Pakshir; Hamed Fasihinia; Shahram Hamedani (BMC Oral Health)
Abstract Background Molariform second premolar is a rare dental anomaly where the second premolar resembles a molar in size and shape. This condition is often linked to macrodontia, a rare enlargement of teeth that disrupts dental proportions and can manifest in isolated, relative, or generalized forms. Although mandibular second premolars are more prone to morphological variability, the occurrence of bilateral molariform premolars, induced by a unique form of gemination, is exceptionally uncommon and infrequently documented, thus making this case clinically significant. Case presentation This case report illustrates a rare bilateral presentation of molariform second premolars in the mandibular arch of a young patient. Both premolars displayed exaggerated mesiodistal dimensions, molar-like occlusal morphology with multiple cusps, and disproportionate faciolingual dimensions. Diagnosis was established through detailed clinical examination and radiographic evaluations. The report explores the treatment challenges posed by the enlarged tooth size and abnormal morphology, including their impact on orthodontic alignment and restorative planning. The patient was scheduled for reshaping of the macrodont premolars after finishing orthodontic treatment, which was planned for correction of overjet, overbite, as well the deep curve of spee. Conclusions Molariform premolars, though uncommon, have a profound impact on dental alignment and treatment outcomes. Their morphological uniqueness might potentially be ignored; therefore, dental professionals should remain vigilant for such anomalies during routine examinations to prevent complications like crowding, malocclusion, and caries. Early diagnosis and strategic intervention are crucial for prevention and interdisciplinary management of unexpected complications during dental procedures. This case emphasizes the importance of routine examination and interdisciplinary collaboration in identifying and treating such anomalies.